2019
DOI: 10.1039/c9gc02306b
|View full text |Cite
|
Sign up to set email alerts
|

Novel deep eutectic solvents with different functional groups towards highly efficient dissolution of lignin

Abstract: Two types of novel deep eutectic solvents with different functional groups were designed for highly efficient dissolution of different types of lignin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(63 citation statements)
references
References 50 publications
0
63
0
Order By: Relevance
“…[ 150–152 ] Notably, the existence of ester and CC bonds enables the interlinkage of three kinds of structural units into a 3D network structure. [ 153–155 ] The combination of these unique features affords lignin an ideal carbon source to prepare hard carbons. [ 156–158 ] Dou et al.…”
Section: Classification and Optimization Strategies Of Hard Carbonsmentioning
confidence: 99%
“…[ 150–152 ] Notably, the existence of ester and CC bonds enables the interlinkage of three kinds of structural units into a 3D network structure. [ 153–155 ] The combination of these unique features affords lignin an ideal carbon source to prepare hard carbons. [ 156–158 ] Dou et al.…”
Section: Classification and Optimization Strategies Of Hard Carbonsmentioning
confidence: 99%
“…Francisco et al reported that DESs have high lignin solubility and very poor or negligible cellulose solubility, [69] and the properties of DESs can be easily tuned by changing the HBDs and HBAs. [70] Mechanism investigation revealed that the functional groups in the DESs significantly affected their ability to dissolve lignin, [71] and they evaluated the potential of DESs for lignin processing more closely. Jablonský et al found that the best fractionation of wheat straw (based on the selectivity of lignin removal) was a DES composed of ChCl with lactic acid (1 : 10) compared with choline chloride with urea (1 : 2), malonic acid (1 : 1), lactic acid (1 : 9; 1 : 10), malic acid (1 : 1).…”
Section: Deep Eutectic Solvent Fractionationmentioning
confidence: 99%
“…reported that DESs have high lignin solubility and very poor or negligible cellulose solubility, and the properties of DESs can be easily tuned by changing the HBDs and HBAs . Mechanism investigation revealed that the functional groups in the DESs significantly affected their ability to dissolve lignin, and they evaluated the potential of DESs for lignin processing more closely. Jablonský et al.…”
Section: Fractionation From Lignocellulosic Biomassmentioning
confidence: 99%
“…This structure makes it possible for lignin to form uniform hydrophilic nano-micelles in aqueous solutions [ 46 ]. DES has been proven to solubilize lignin effectively [ 47 , 48 , 49 ], and ChCl and ETA are the most promising candidates for industrial applications because of their low viscosity, environmentally friendly and biodegradable nature. In this regard, herein we propose DES composed of ChCl and ETA as a novel dissolution system for the LNPs preparation.…”
Section: Resultsmentioning
confidence: 99%